EQRbot: A chatbot delivering EQR argument-based explanations - Castagna, Federico; Garton, Alexandra; McBurney, Peter; Parsons, Simon; Sassoon, Isabel; Sklar, Elizabeth I. (Frontiers in Artificial Intelligence, 2023)
Recent years have witnessed the rise of several new argumentation-based support systems, especially in the healthcare industry. In the medical sector, it is imperative that the exchange of information occurs in a clear and accurate way, and this has to be reflected in any employed virtual systems. Argument Schemes and their critical questions represent well-suited formal tools for modelling such information and exchanges since they provide detailed templates for the explanations to be delivered. This paper details the EQR argument scheme and deploys it to generate explanations for patients' treatment advice using a chatbot (EQRbot). The EQR scheme (devised as a pattern of Explanation-Question-Response interactions between agents) comprises multiple premises that can be interrogated to disclose additional data. The resulting explanations, obtained as instances of the employed argumentation reasoning engine and the EQR template, will then feed the chatbot that will exhaustively convey the requested information and answers to follow-on users' queries as user-personalised Telegram messages.